Development and Application of Herbal Medicine from Marine Origin - Sung, Ping-Jyun (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Marine herbal medicine generally refers to the use of marine plants as original materials to develop crude drugs, or for other medical purposes. The term 'marine plants' usually denotes macroalgae grown between intertidal and subintertidal zones, including Chlorophyta, Phaeophyta, and Rhodophyta. Considerable progress has been made in the field of biomedical research into marine microalgae and microorganisms in the past decade. As the most important source of fundamental products in the world, marine plants have a very important role in biomedical research. Furthermore, worldwide studies have consistently demonstrated that many crude drugs derived from marine plants contain novel ingredients that may benefit health or can be used in the treatment of diseases; some have been developed into health foods, and some even into drugs. It is expected that there are many substances of marine plant origin that will have medical applications in terms of improving human health and are awaiting discovery.<false,>In this Special Issue, entitled "Development and Application of Herbal Medicine of Marine Origin", we will provide a platform for researchers to publish biomedical studies on substances of marine plant origin. We welcome submissions from scientists and academics from across the world.